Islamic movements in Africa and their impact on African security, Boko Haram as a model (Journal of the College of Basic Education, 2022)
This movement arose in 2003, and it is considered a movement with ancient origins in the Islamic resistance against British colonialism and its administration, and in the period that followed independence, in opposition to the military and civilian governments that showed complete disregard for the Middle East region. And that region in particular suffered greatly from desertification, a large increase in the population, and suffered from a lack of investment, and the inhabitants of this region are among the poorest regions in Nigeria, and their poverty increases in large proportions with the progress of time. The wealthy elites in the northeastern region, who get rich by killing and smuggling weapons, still participate in the secular movement, while remaining significantly distant from the population of the region.